Understanding Criminal Punishment and Prisons in China - Wu, Wei (The prison journal, 2018)
This article provides an interpretation of the evolution of criminal punishment and prisons in China from an historical perspective. The historical investigation reveals that the current ganhua and paternalistic or fatherly approaches to prison corrections are expressions of an underlying cultural tradition that is deep and abiding. However, the existence of the paradoxical goals of punishment and reformation at the level of the implementation of prison sentences, which can erode the protection of the rights of prisoners, is contingent upon political and legal decisions that can be changed by acts of law and legal reform.